Perilaku Komunikasi Petani dalam pencarian Informasi Pertanian Organik (Kasus Petani bawang merah Di Desa Srigading Kabupaten Bantul) - Ikhsan Fuady; Djuara P. Lubis; Richard W.E. Lumintang (Jurnal Komunikasi Pembangunan, 2012)
Abstraks Sustainable agriculture development holds an important issue now days.  Famers’ Communication behaviors in information seeking constitute a pivotal position in order to increase the farmers’ autonomy.  The objectives of this research were: (1) to describe farmers’ communication behavior of organic agriculture cultivation in red-onion farmers, (2) to analyze the correlation between farmers’ communication behavior and red-onion organic agriculture practices, This research was designed qualitatively using survey method.  The data was analyzed using Tau-Kendall Test.  This research produced several results such as: an Organic practice that has been conducted by the farmers was not utterly organic.  The organic performer’s behavior was influenced by communication behavior variable and individual characteristics’.  The farmers’ Autonomy was much correlated with farming activities’ behavior. Key words: communication behavior, organic agriculture, red - onion